Растратчики: повести и рассказы / Валентин Катаев - Катаев Валентин Петрович (Советский писатель, 1990)
Экземпляры: Аб (20150219) / Инвентарный номер: 102137 / Цена: 15.00 / Авт.знак: К 29 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6